2017
DOI: 10.1093/jhered/esx071
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Rice Seed OMICS in Low-Level Gamma Radiation Environment in Iitate Village, Fukushima

Abstract: Here, we present an update on the next level of experiments studying the impact of the gamma radiation environment, created post-March, 2011 nuclear accident at Fukushima Daiichi nuclear power plant, on rice plant and its next generation-the seed. Japonica-type rice (Oryza sativa L. cv. Koshihikari) plant was exposed to low-level gamma radiation (~4 μSv/h) in the contaminated Iitate Farm field in Iitate village (Fukushima). Seeds were harvested from these plants at maturity, and serve as the treated group. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Overall there have been very few studies of the effects of radiation on plants related to the Fukushima event. Notable exceptions include studies of tree growth mentioned above, and studies of rice by Hayashi et al (2014Hayashi et al ( , 2015 and Rakwal et al (2018) that have suggested effects on plant growth, DNA repair, stress responses, and an array of gene expression responses. These studies are likely to be very useful for further investigations of mechanisms associated with genetic and physiological responses to chronic radiation exposures.…”
Section: Plant Growth and Radiationmentioning
confidence: 99%
“…Overall there have been very few studies of the effects of radiation on plants related to the Fukushima event. Notable exceptions include studies of tree growth mentioned above, and studies of rice by Hayashi et al (2014Hayashi et al ( , 2015 and Rakwal et al (2018) that have suggested effects on plant growth, DNA repair, stress responses, and an array of gene expression responses. These studies are likely to be very useful for further investigations of mechanisms associated with genetic and physiological responses to chronic radiation exposures.…”
Section: Plant Growth and Radiationmentioning
confidence: 99%
“…Field observations of the possible biological effects of radioactive contamination after the Fukushima nuclear accident have been reported in various organisms, including bird and arthropod populations [1,2], gall-forming aphids [3], Japanese monkeys [4,5,6], barn swallows [7], goshawks [8], rice plants [9,10], fir trees [11], red pine trees [12], and intertidal species populations, including the rock shells [13]. Similarly, the possible changes induced by the nuclear accident have been reported in cattle at the biochemical level [14] and in pigs at the gene expression level [15].…”
Section: Introductionmentioning
confidence: 99%
“…Biological impacts of the Chernobyl accident have been documented in birds 1116 , and more recently, those data were examined in a meta-analysis 17 . Several field studies have documented the effects of the Fukushima nuclear accident on various organisms: bird and arthropod populations 1820 , gall-forming aphids 21 , Japanese monkeys 22–25 , barn swallows 26 , goshawks 27 , rice plants 28,29 , fir trees 30 , red pine trees 31 , and populations of intertidal species including the rock shell 32 . At the biochemical level, stress responses might have been induced in cattle in the contaminated areas 33 .…”
Section: Introductionmentioning
confidence: 99%